God's plan? The role of emotional repression in forming and sustaining religious beliefs. Issue 4 (2nd October 2021) - Swan, Thomas; Halberstadt, Jamin
ABSTRACT: The motivational account of religion—that belief fulfills a psychological need—has been both historically popular and empirically supported. It is also potentially informative about religious interpretations of negative events (e.g., that they are part of God's benevolent plan). Yet, it is not clear what cognitive mechanism(s) might link negative events to religious belief, and what motivates belief in gods that cause these events. We proposed that a repressive coping style is an important factor because it involves an interpretive bias that both downplays threat and also emphasizes benefits afforded by ambivalent stimuli (including god concepts), potentially facilitating the construction of supernatural concepts that are positive and relevant enough to attract and sustain belief. In the current research, across three studies, we found that repressors were more likely to be religious, and more likely to interpret familiar, unfamiliar, and experimenter-created gods positively. Repression partially explained the positive views of gods held by religious individuals, and this relationship strengthened when distressing events were associated with gods, suggesting that repression helps to sustain belief. Furthermore, the relationship between repression and belief in familiar and unfamiliar gods was partially explained by god positivity, supporting a motivated reasoning account of belief formation.